The impact of the Digitalization of E-Samsat and Samsat Corner on Improving Administrative Convenience in Motorcycle Tax Collection - Ozalia, Elza Rizqy; Sahila; Rusmida; Tobing, Shelly Farida; Frastuti, Melia (Indonesian Journal of Accounting and Governance, 2025)
The digitalization of public tax services has become a strategic instrument for improving administrative efficiency and taxpayer convenience. This study examines the impact of e-Samsat digitalization and Samsat Corner services on administrative convenience in motorcycle tax collection at Samsat Palembang 1. Using a quantitative explanatory approach, data were collected from 100 motorcycle taxpayers who utilized both digital and offline service innovations. Multiple regression analysis shows that both e-Samsat and Samsat Corner have a positive and significant effect on administrative convenience, with Samsat Corner demonstrating a stronger influence (β = 0.557) compared to e-Samsat digitalization (β = 0.153). The model explains 31.7% of the variance in administrative convenience, indicating that service innovation plays a substantial, though not exclusive, role in improving tax administration. This study contributes to the existing literature by specifically focusing on two-wheeled motor vehicle taxpayers, a segment that has received limited empirical attention despite its dominance in urban vehicle ownership. Unlike prior studies that primarily assess digital tax systems in general or emphasize taxpayer compliance, this research positions administrative convenience as a key outcome variable from the taxpayer’s perspective. Furthermore, the findings highlight the complementary role of digital and physical service innovations, suggesting that digitalization alone is insufficient without accessible offline service points. These results provide empirical support for integrated public service strategies that combine digital platforms with inclusive, on-site tax services.